Integrating construactability into the design process - Woon, Kai Siong (2006)
Constructability is an important element in building project’s design phase, where designers’ personnel play a prominent role to enhance it. Several researchers found that failure of design professional to consider constructability during the design phase can result design reworks, contract changes, delay, increase of cost, and even legal entanglement and claims. The focus of this study is establishment and integration of constructability principles into the current building’s design process. Therefore, the objectives of this study are to determine the local construction industry’s current design process, in order to propose an integration of design constructability review process to that existing design process model, and develop a building design constructability checklist. There are three distinct phases of this study: phase 1 involves literature review and preliminary interview; phase 2 consists of structured interviewing with design professional experts and design process models development; phase 3 comprises of constructability principles integration and the checklist development. The data flow diagram (DFD) is adopted in this study to model those design process flow. Finally, the outcomes of this study are establishment of general building design process model, constructability integrated building design process model and constructability checklist. This checklist acts as a tool, where it is integrated with constructability principles, used for constructability enhancement of the design. However, due to the limitation of time, only a foundation design constructability checklist is developed.